Ethics in the nursing care to patients on haemodialysis treatment - Janairy Rosales Origuela; Jayce Díaz Díaz; Beatriz Molina Ramírez; Osmel Chávez Troya (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2016)
Patients with chronic terminal renal failure, treated with haemodialysis, have experienced a significant increase in Cuba, similarly to more developed countries. Although there is no question that haemodialysis is effective to extend the patient's with nephropathies lives, there is a considerable controversy with respect to this survival, even when new dialysis modalities have focused in the potential benefits they offer to improve the quality of life of the affected patients. The nursing personnel play an important role in the assistance to these patients, for this reason it is imperative, then, to know how to establish the links between ethics and nursing care in the haemodialysis service which is the objective of this work.